2014
DOI: 10.3389/fonc.2014.00127
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Therapeutic Roles of Exosomes in Cancer

Abstract: The role of exosomes in cancer development has become the focus of much research, due to the many emerging roles possessed by exosomes. These micro-vesicles that are ubiquitously released in to the extracellular milieu, have been found to regulate immune system function, particularly in tumorigenesis, as well as conditioning future metastatic sites for the attachment and growth of tumor tissue. Through an interaction with a range of host tissue, exosomes are able to generate a pro-tumor environment that is ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(173 citation statements)
references
References 78 publications
3
160
0
10
Order By: Relevance
“…It has been noted that cancer cells secrete much higher amounts of exosomes in comparison to non-transformed cells (26). Exosomes are involved in initiation, growth, progression and drug-resistance of tumors involving interactions with the microenvironment by transferring oncogenic proteins and nucleic acids (15,19,27,28).…”
Section: Exosomes -Functions In Cancermentioning
confidence: 99%
“…It has been noted that cancer cells secrete much higher amounts of exosomes in comparison to non-transformed cells (26). Exosomes are involved in initiation, growth, progression and drug-resistance of tumors involving interactions with the microenvironment by transferring oncogenic proteins and nucleic acids (15,19,27,28).…”
Section: Exosomes -Functions In Cancermentioning
confidence: 99%
“…Therefore, studies aiming to achieve cancer-derived exosome depletion from the circulation could be promising for the development of novel therapeutics that would mitigate tumor metastasis. 26,27 In this study, we demonstrated the therapeutic concept of suppressing cancer metastasis via the depletion of cancer-derived EVs. Antibodies to human-specific CD9 and CD63, which are considered to localize at the surface of most exosomes, 28 were utilized to inhibit the pro-metastatic effects of cancer-derived exosomes.…”
Section: Introductionmentioning
confidence: 99%
“…5). Important (patho)physiological functions of EVs are increasingly recognized in different research areas including immunology (6,7), cardiovascular disorders (8), and cancer biology (9). From a clinical perspective the dynamic population of body fluid-derived EVs attracts much attention as potential biomarker and non-invasive liquid biopsy (5).…”
mentioning
confidence: 99%